2021
DOI: 10.1007/s00383-021-04971-6
|View full text |Cite
|
Sign up to set email alerts
|

Children with congenital colorectal malformations during the UK Sars-CoV-2 pandemic lockdown: an assessment of telemedicine and impact on health

Abstract: Purpose This pilot study was designed to assess bowel function and quality of life (QoL) in children and adolescents with congenital colorectal malformations (CCM) during the first UK COVID lockdown period. Methods Changes in health were assessed through semi-structured interviews, gastrointestinal functional outcomes using Krickenbeck scoring and QoL by the modified disease-specific HAQL (Hirschsprung’s disease anorectal malformation quality of life quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Out of 345 articles identified by the database searches, 49 articles met the inclusion criteria. 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Most concerned esophageal atresia ( n = 17) and Hirschsprung's disease ( n = 14). None of the articles focused on duodenal atresia or omphalocele.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 345 articles identified by the database searches, 49 articles met the inclusion criteria. 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Most concerned esophageal atresia ( n = 17) and Hirschsprung's disease ( n = 14). None of the articles focused on duodenal atresia or omphalocele.…”
Section: Resultsmentioning
confidence: 99%
“…Institutions report up to 72% of patients undergoing BMP remotely with improved continence after the visits and decreased rate of stress for the patients and their families compared to in-person visits [ 39 ]. A single institution study showed that among colorectal patients after their reconstruction, 44% of families (all of which had children with severe malformations) preferred in-person visits to telephone calls [ 40 ]. This might result from the absence of face-to-face contact during a telephone consultation that could be ensured using video technologies.…”
Section: Long-term Collaboration and Bowel Management Programmentioning
confidence: 99%